Probiotic Bacillus cereus Strains, a Potential Risk for Public Health in China - Zhu, Kui; Hölzel, Christina S.; Cui, Yifang; Mayer, Ricarda; Wang, Yang; Dietrich, Richard; Didier, Andrea; Bassitta, Rupert; Märtlbauer, Erwin; Ding, Shuangyang (Frontiers in Microbiology, 2016)
Bacillus cereus is an important cause of foodborne infectious disease and food poisoning. However, B. cereus has also been used as a probiotic in human medicine and livestock production, with low standards of safety assessment. In this study, we evaluated the safety of 15 commercial probiotic B. cereus preparations from China in terms of mislabeling, toxin production, and transferable antimicrobial resistance. Most preparations were incorrectly labeled, as they contained additional bacterial species; one product did not contain viable B. cereus at all. In total, 18 B. cereus group strains – specifically B. cereus and B. thuringiensis – were isolated. Enterotoxin genes nhe, hbl, and cytK1, as well as the ces-gene were assessed by PCR. Enterotoxin production and cytotoxicity were confirmed by ELISA and cell culture assays, respectively. All isolated B. cereus group strains produced the enterotoxin Nhe; 15 strains additionally produced Hbl. Antimicrobial resistance was assessed by microdilution; resistance genes were detected by PCR and further characterized by sequencing, transformation and conjugation assays. Nearly half of the strains harbored the antimicrobial resistance gene tet(45). In one strain, tet(45) was situated on a mobile genetic element – encoding a site specific recombination mechanism – and was transferable to Staphylococcus aureus and B. subtilis by electro-transformation. In view of the wide and uncontrolled use of these products, stricter regulations for safety assessment, including determination of virulence factors and transferable antimicrobial resistance genes, are urgently needed.